Hubungan Kemandirian Activity Daily of Living dengan Kepuasan Hidup Lansia Pedesaan - Puspitosari, Aniek; Nurhidayah, Ninik (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: Independence in performing Activities of Daily Living (ADL) is a key indicator of quality of life among the elderly. Older adults who are able to carry out ADL independently tend to report higher levels of life satisfaction. However, rural areas have distinct social and environmental characteristics compared to urban settings, which may influence this relationship. Objectives: This study aims to examine the relationship between the level of ADL independence and life satisfaction among older adults living in rural areas of Karanganyar Regency. Methods: This research employed an analytical quantitative design with a cross-sectional approach. A total of 100 older adults were selected through purposive sampling from several villages in Karanganyar Regency. The instruments used were the Katz Index for ADL and the Satisfaction With Life Scale (SWLS) for measuring life satisfaction. Data were analyzed using the Cho-Square correlation test. Results: The results showed a significant relationship between ADL independence and life satisfaction among the elderly (p = 0.002; α < 0.05). Older adults who were independent in performing ADL tended to report moderate to high levels of life satisfaction compared to those who were not independent. Conclusion: There is a positive and significant relationship between independence in daily activities and life satisfaction among older adults in rural areas of Karanganyar Regency. Enhancing community-based assistance and rehabilitation programs can support elderly independence and improve their quality of life. Keywords: Aging, KATZ Index, Health community, Satisfaction of Life